Struggles to Improve Students' Entrepreneurship Interest Through GEPPRAK Learning Model - Irmawati, Irmawati; Murtini, Wiedy; Hakim, Lukman (Fakultas Ekonomi, Universitas Negeri Semarang, 2020)
This study aims to investigate the implementation of